(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
A wireless power transfer (WPT) system transfers an alternating current (AC) power from a TC (transmitter coil) to a RC (receiver coil), using an electromagnetic field concept. Several previous reports on WPT systems were able to transmit this power, although their AC frequencies were high in some kilohertz or megahertz (kHz or MHz). These frequencies were unable to be applied directly on the AC loads or only administered to the direct current (DC) energy after rectification through a rectifier circuit. In the receiver phase, the AC power was also very low, due to the minimum voltage and current on the RC. Therefore, this study aims to determine the effects of temperature and solar irradiance on the performance of the 50 Hz photovoltaic wireless power transfer (PVWPT) system. This system is constructed by some PV modules in series connection, to achieve a required DC voltage level on the DC-DC converter and receiver phase. It also converts DC to AC voltages on the TC (transmitter coil) of an H-bridge inverter, with a receiver circuit and a magnetic relay coil positioned between the TC and RC (transmitter and receiver coil). The results showed that solar irradiance and temperature affected the performances of the PV module and PVWPT system. This indicated that higher solar irradiance increased the performance of the PVWPT system, whose maximum efficiency was achieved by positioning the magnetic relay coil between the TC and RC.